INTEGRATION OF MODERN TECHNOLOGIES INTO THE SYSTEM OF QUALITY MANAGEMENT OF EDUCATIONAL SERVICES - Makhmudalieva Mahmudakhon Jakhongir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In recent decades, the global education sector has undergone numerous transformations, influenced by the growing demands of society for high-quality educational services. The ever-increasing pace of technological advancement has inevitably impacted educational institutions, prompting a critical need to integrate modern technologies into their quality management systems. Effective quality management in the sphere of educational services remains essential for not only ensuring academic excellence but also for enhancing the overall satisfaction of stakeholders, including students, educators, employers, and the wider community.